The valence conversion mechanism for Mo‐doped VO2 films with enhanced thermochromic properties. Issue 14 (19th May 2022) - Pei, Rui; Ma, Xinguo; Han, Changcun; Liu, Zhifeng; Cheng, Zhengwang; Dong, Xiaoru
Abstract: Reducing the phase transition temperature ( T c ) of VO2 films to achieve the application in the field of Smart Home is still a challenge. Thus, in the work, the ultra‐thin VO2 films with different Mo doping amounts were successfully prepared by an economic sol‐gel method and atmosphere annealing, aiming to further investigate the mechanism of the decrease of T c . The results show that the VO2 films with 3 at % Mo doping possess the T c of 29.5 °C. Notedly, in the as‐prepared films, the maximum transmittance in the visible region ( T vis ) is 46.3 % and the solar direct transmittance ( T sol ) is 45.8 %. According to the XPS spectra, it is confirmed that the Mo doping prominently induces the valence change of V ions from +4 to +3, inhibiting the strain in the phase transition process of VO2 films, and leading to the decrease of T c . Our work will provide a feasible solution for reducing the T c of the ultra‐thin VO2 films. Abstract :